DETERMINATION OF 70% Ethanol EXTRACT FLAVONOID TOTAL LEVELS BINAHONG (Anredera cordifolia [Ten] Steenis) LEAVES IN PELEM VILLAGE, TANJUNGANOM, KAB. NGANJUK - Wiwik Werdiningsih; Nurjanah Tia Pratiwi; Ninis Yuliati (Fakultas Sains, Teknologi, dan Analsisi Institut ilmu Kesehatan Bhakti Wiyata, 2022)
Binahong leaves (Anredera cordifolia [Ten] Steenis) belonging to the Basellaceae family contain flavonoid compounds, saponins, and polyphenolic alkaloids. The largest secondary metabolites of phenolic compounds are flavonoids which have pharmacological effects such as antioxidants. This study aims to determine the flavonoid content of binahong leaves (Anredera cordifolia [Ten] Steenis) from Pelem village in 70% ethanol solvent. This study uses a pure experimental method. The extract was obtained by maceration method with 70% ethanol as solvent. The maceration process was carried out for 3 days with repeated maceration 2 times and occasionally shaking. After the viscous extract was obtained, qualitative tests were carried out for flavonoid screening and determination of flavonoid content using UV-Vis spectrophotometry. The qualitative test results of 70% ethanol extract proved to contain flavonoids. Based on the results of this study, it can be concluded that the determination of total flavonoid levels using the UV-Vis spectrophotometer method was obtained at 0.1842% (w/w).